Strategies adopted by maize farmers to minimize post-harvest losses in Delta State, Nigeria - Ovharhe, O. J.; Emaziye, P. O.; Okpara, O.; Agoda, S.; Benson, C. O. (International Journal of Agricultural Technology, 2021)
The study assessed the strategies which is adopted by maize farmers to minimize post-harvest losses in Delta State, Nigeria. The results showed that major causes of post-harvest losses were inadequate awareness of modern storage facilities ( = 3.74). Respondents experienced post-harvest losses on a maximum level at storage structure ( = 3.64). It was noticed that there were poor extension activities and visits ( = 0 .26) and zero beneficiaries of incentives for storage activities from the government ( = 0.00). One of the most effective strategies adopted to minimize post-harvest losses was the use of bags for storage ( = 3.06). A high degree of mean constraints was the limited capacity of institutional support to post-harvest activities ( = 3.78) and the use of less efficient processing technology ( = 3.73). Results revealed that significant relationship (p<0) exit among marital status, education and age of respondents and perceived strategies to minimize post-harvest losses among maize farmers. It was concluded among other factors that poor extension activities affected post-harvest management and the sorting of grains was a better strategy adopted to minimize post-harvest losses